Genetic Pathways and Functional Subnetworks for the Complex Nature of Bipolar Disorder in Genome-Wide Association Study - Kuo, Chan-Yen; Chen, Tsu-Yi; Kao, Pei-Hsiu; Huang, Winifred; Cho, Chun-Ruei; Lai, Ya-Syuan; Yiang, Giou-Teng; Kao, Chung-Feng (Frontiers in Molecular Neuroscience, 2021)
Bipolar disorder (BPD) is a complex psychiatric trait that is also recognized as a high substantial heritability from a worldwide distribution. The success in identifying susceptibility loci for BPD has been limited due to its complex genetic architecture. A growing evidence from association studies including genome-wide association (GWA) studies points to the need of improved analytics strategies to pinpoint the missing heritability for BPD. More importantly, many studies indicate that BPD has a strong association with dementia. We conducted advanced pathway analytics strategies to investigate synergistic effects of multilocus within biologically functional pathways, and further demonstrated functional effects among proteins in subnetworks to examine mechanisms underlying the complex nature of bipolar using a GWA dataset for BPD. We allowed bipolar susceptible loci to play a role that takes larger weights in pathway-based analytic approaches. Having significantly informative genes identified from enriched pathways, we further built function-specific subnetworks of protein interactions using MetaCore. The gene-wise scores (i.e. minimum p-value) were corrected for the gene-length, and the results were corrected for multiple tests using Benjamini & Hochberg’s method. We found 87 enriched pathways that are significant for BPD; of which 36 pathways were reported. Most of them are involved with several metabolic processes, neural systems, immune system, molecular transport, cellular communication and signal transduction. Three significant and function-related subnetworks with multiple hotspots were reported to link with several GO processes for BPD. Our comprehensive pathway-network frameworks demonstrated that the use of prior knowledge is promising to facilitate our understanding between complex psychiatric disorders (e.g. BPD) and dementia for the access to the connection and clinical implications, as well as the development and progression of dementia.